Full cycle evolution law of energy-stress in the surrounding rock of the gob-side entry driving for adjacent advancing working face - Dingchao CHEN; Xiangyu WANG; Jianbiao BAI; Menglong LI; Jianfei LU; Feiteng ZHANG; Shiqi SUN; Xiangqian ZHAO; Yang YU (Meitan kexue jishu)
The full cycle dynamic pressure impact of the lateral basic roof fracture, rotation, and sinking of the upward working face along the gob excavation roadway in the face of mining is significant, and the roadway deformation is difficult to maintain. This article takes the 15105 panel of Wenzhuang Coal Mine as the engineering background, and proposes to change the excavation trajectory of the roadway behind the unstable gob of 15103 panel, on the basis of the original 25 m coal pillar facing the gob, and reduce the width of the section coal pillar to 6 m for gob excavation. In order to demonstrate the feasibility of the plan, a numerical model was established using FLAC3D to simulate the evolution law of the energy stress full cycle of the surrounding rock of the roadway (driven heading for mining of 15103 panel, excavation of the unstable gob side roadway, and mining of the 15105 panel) under two scenarios: the original plan and the optimized plan. The simulation results show that: ① During driven heading for mining of 15103 panel, stress and energy are mainly concentrated on the gob side of the section coal pillar. ② During the excavation of the unstable gob side roadway, compared with the original plan, the optimized plan transferred the internal energy and stress of the 6 m coal pillar to the coal body side of the working face ③ During the mining period of the 15105 panel, when adopting the original plan, both energy and stress were concentrated towards the mining side of the 25 m coal pillar, with a peak stress of 31.2 MPa and a maximum energy of 192.4 kJ/m3. When adopting the optimization plan, both energy and stress are transferred to the solid coal side of the working face. The 6 m coal pillar has a certain bearing capacity, and the stress concentration is low and there is no obvious energy accumulation throughout the process. During the mining period, the peak stress inside the 6 m coal pillar is only 8.1 MPa, and the maximum energy is 126.7 kJ/m3. On this basis, the reliability of the optimization plan was determined, and combined with numerical simulation results and on-site geological conditions, it is proposed to divide the roadway into four sections: the face to face mining section, the gob excavation section, the gradient coal pillar section, and the gob excavation section. A zoning control system for the surrounding rock of the roadway was established, and anchor bolt support parameters were designed. Finally, industrial experiments were successfully conducted, and on-site monitoring results showed that the overall control effect of each section of the roadway was good.